COVID-19 vaccine impact on seizure control in patients with epilepsy: insights from Saudi Arabia - Ziyad Althani; Sirin Almulhim; Shaikhah Al-Dossary; Asma Alruwaili; Shahid Bashir (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background The COVID-19 pandemic poses distinctive challenges for individuals with epilepsy, necessitating an exploration of the impact of COVID-19 vaccination on seizure control. The main aim of the study is to assess the impact of the COVID-19 vaccine on seizure frequency among patients with epilepsy in Saudi Arabia. A cross-sectional study involving 67 participants diagnosed with epilepsy in Saudi Arabia collected demographic information, COVID-19 vaccination status, and willingness for vaccination, side effects experience, and changes in seizure frequency during the pandemic. Statistical analyses, including logistic regression, investigated the association between COVID-19 vaccination and changes in seizure frequency. Results The study delves into the diverse impact of the COVID-19 period and associated lockdown on individuals with epilepsy, each with their unique experiences. Some experienced a decrease (11.9%), some an increase (23.9%), while a significant portion observed no significant change in seizure frequency during this period (64.2%). These individual experiences highlight the complexity of managing epilepsy during a pandemic. Conclusion This research illuminates the intricate relationship between COVID-19 vaccination and seizure control in individuals with epilepsy in Saudi Arabia. The results emphasize the necessity of personalized strategies for managing epilepsy amid the pandemic. Additional research and ongoing monitoring are crucial to refine comprehension and improve care for this susceptible group.